2022
DOI: 10.1002/adsc.202200161
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Phosphoric Acid‐Catalyzed Enantioselective Formal [4+2] Cycloaddition Between Dienecarbamates and 2‐Benzothioazolimines

Abstract: An enantioselective chiral phosphoric acid catalyzed formal [4+2] cycloaddition between 2‐benzothiazolimines and N‐H‐1,3‐dienecarbamates is described. A divergence in reaction pathways was observed depending on the dienes employed. The reaction performed with 4‐substituted dienes produced benzothiazolopyrimidines as major product in yields ranging from 42 to 67%, as single diastereoisomer and with enantioselectivity between 93 and 99%. The same reaction performed with 3‐substituted dienes, however, gave highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 88 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…[48] In the presence of only 2 mol% Cat. 8 at room temperature, the reaction is carried out using ortho-hydroxyphenyl-substituted para-quinone methides (59) and enamides (60) as substrates. This cycloaddition reaction accommodated a wide variety of ortho-hydroxyphenyl p-QMs (59) with both electron-donating and electron-withdrawing substituents as well as enamides (60) with various substituents on the aryl moiety to produce the corresponding acetamido-substituted tetrahydroxanthenes (61) with three adjacent stereogenic centers in high yields (up to 99 %) and excellent stereoselectivities (up to > 99 : 1 dr and up to 98 % ee) (Scheme 18).…”
Section: Stereoselective [4 + 2] Cycloaddition and Annulation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[48] In the presence of only 2 mol% Cat. 8 at room temperature, the reaction is carried out using ortho-hydroxyphenyl-substituted para-quinone methides (59) and enamides (60) as substrates. This cycloaddition reaction accommodated a wide variety of ortho-hydroxyphenyl p-QMs (59) with both electron-donating and electron-withdrawing substituents as well as enamides (60) with various substituents on the aryl moiety to produce the corresponding acetamido-substituted tetrahydroxanthenes (61) with three adjacent stereogenic centers in high yields (up to 99 %) and excellent stereoselectivities (up to > 99 : 1 dr and up to 98 % ee) (Scheme 18).…”
Section: Stereoselective [4 + 2] Cycloaddition and Annulation Reactionsmentioning
confidence: 99%
“…Recently, Masson and co‐workers disclosed an asymmetric chiral phosphoric acid catalyzed construction of benzothiazolopyrimidines ( 86 ) via formal [4+2] cycloaddition between 2‐benzothiazolimines ( 83 ) and 4‐substituted dienes ( 84 ) in moderate to good yields with high enantioselectivities and as single diastereoisomer (Scheme 26). [59] Various imines bearing methoxy, methyl, cyanide or halogens either at the benzo[d]thiazol‐2‐yl or at the aromatic ring and 1,3‐dien‐1‐yl carbamates with benzyl‐protected (NHCbz), methylcarbamate or S‐benzylcarbamothioate and sterically demanding δ‐substituted alkyl side chains such as methyl, isobutyl, isopropyl or 2,6‐dimethylhept‐5‐enyl were tolerable in this transformation to afford the corresponding chiral benzothiazolopyrimidines. However, the authors reported that, the incorporation of ortho substitution at either aromatic end of imines ((o‐tolyl)methanimine or 4‐methylbenzo[d]thiazol‐2‐yl) was not tolerable.…”
Section: Cycloaddition Reactionsmentioning
confidence: 99%
“…12 e As we all know, the Diels–Alder reaction is an efficient and straightforward method to construct six-membered functionalized nitrogen-containing heterocycles. 3,13 In 1985, Grieco and co-workers reported a aza-Diels–Alder reaction between electron-rich 1,3-dienes and simple iminium salts in aqueous solution to construct tetrahydropyridine derivatives. 3 a However, to the best of our knowledge, the inverse-electron-demand (IED) aza-Diels–Alder reaction between electron-deficient 1,3-dienes (CC–CC, all-carbon) and 1,3,5-triazinanes to construct tetrahydropyridines has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only one enantioselective methodology has been proposed by Biju et al in which N -heterocyclic carbene promoted (3 + 3)-annulation between 2-bromoenals and β-oxodithioesters to provide dihydrothiopyranones in high enantioselectivities (Scheme a) . Therefore, the development of a novel stereocontrolled synthetic route for the construction of dihydrothiopyranones is still highly desirable and meets our longtime interest in the asymmetric synthesis of heterocyclic scaffolds …”
mentioning
confidence: 99%